Effects of work on reproductive and productive performance of cross-bred dairy cows in the Ethiopian highlands - Agyemang, K.; Astatke, A.; Anderson, F.M.; Wolde-Mariam, W.A. (Springer, 1991)
Reports the effect of draught on milk production, reproductive and productive performance of crossbred dairy cows which had completed the first two lactations. Evaluates ways and means of reducing the effective number of draught animals needed to support agricultural production in the Ethiopian highlands.